2012
DOI: 10.1590/s1517-83822012000400014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of genotypes in Helicobacter pylori isolates from patients in eastern Turkey and the association of these genotypes with clinical outcome

Abstract: There is not much information available regarding the prevalence of the genotypes of Helicobacter pylori isolates in Turkey, particularly in eastern Turkey. The aims of this study were to detect the prevalence of different genotypes of H. pylori in Turkish patients with gastrointestinal complaints and to determine the relationship of these genotypes with clinical outcome and sex. One hundred forty H. pylori isolates were examined for the presence of its genotypes by the PCR. We found that the prevalence of vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
4
5
0
1
Order By: Relevance
“…In the current study, the vacA s2 allele was the most predominant genotype (55%) followed by vacA s1 (45%). Our findings are similar to an earlier report from Egypt (Van Doon et al, 1999), Korea (Kim et al, 2001) and Turkey (Ozbey and Aygun, 2012). Al Quabandi et al (2005) reported that North Africans were predominantly infected with the s2 type.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, the vacA s2 allele was the most predominant genotype (55%) followed by vacA s1 (45%). Our findings are similar to an earlier report from Egypt (Van Doon et al, 1999), Korea (Kim et al, 2001) and Turkey (Ozbey and Aygun, 2012). Al Quabandi et al (2005) reported that North Africans were predominantly infected with the s2 type.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of cagA (38%) in this study was in agreement to previous report from Egypt (El-Garbawy et al, 2006) and lower than recent studies from Turkey (71.4%) (Ozbey and Aygun, 2012), Korea (97%) (Kim et al, 2001), Malaysia (94%) (Ramelah et al, 2005) China (96.3%) (Zhou et al, 2004) and Kuwait (53%) (Al Quabadi et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…As previously reported that the iceA1 and the iceA2 genotypes were, respectively, isolated in 60.2% and in 16% of strains [30]. The iceA1 genotype associated with peptic ulceration in patients [2,16,30,58]. In our study, iceA2 allele was considered predominant and there was no association between iceA2 and cagA status.…”
Section: Resultssupporting
confidence: 53%
“…The iceA gene contains two allelic variants iceA1 and iceA2 [45,58]. Analysis of iceA gene based on PCR assay using primers specific to sequence region of iceA gene, which give products of 247 bp and/or 229/334 bp for iceA1 and iceA2 respectively, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ülkemizde cagA gen bölgesine yönelik PCR tabanlı ve anti-CagA tespitine yönelik serolojik araştırmalar yapılmış olup, bunlar daha ziyade prevalans çalışmalarıdır [28][29][30][31][32][33][34][35] . Bizim çalışmamızda üretilen rekombinant CagA proteini, hasta serumlarında anti-CagA antikorlarının araştırılması amacıyla geliştirilecek olan testlerde kullanılabilir niteliktedir.…”
Section: Discussionunclassified